Functional brain imaging with fMRI and MEG - He, Jiabao (2005)
The work described in this thesis was performed by the author, except where indicated. All the studies were accomplished on the 3 Tesla system within the Magnetic Resonance Centre at the University of Nottingham, and the Wellcome Trust MEG Laboratory at the Aston University during the period between October 1999 and June 2005. Functional Magnetic Resonance Imaging (fMRI) and Magnetoencephalography (MEG) are two promising brain function research modalities, sensitive to the hemodynamic and electrophysiological responses respectively during brain activites. The feasibility of joint employment of both modalities was examined in both spatial and temporal domains. A somatosensory tactile stimulus was adopted to induce simple functional reaction. It was shown that a reasonable spatial correspondence between fMRI and MEG can be established. Attempts were made on MEG recordings to extract suitable aspects for temporal features matching fMRI with a method reflecting the physical principles. It was shown that the this method is capable of exposing the nature of neural electric activities, although further development is required to perfect the strategy.